ChemInform Abstract: A Remarkable Regiocontrol in the Palladium‐Catalyzed Silylstannylation of Fluoroalkylated Alkynes — Highly Regio‐ and Stereoselective Synthesis of Multi‐Substituted Fluorine‐Containing Alkenes. Issue 28 (15th July 2014) - Konno, Tsutomu; Kinugawa, Ryoko; Ishihara, Takashi; Yamada, Shigeyuki
Abstract The Pd‐catalyzed silylstannylation of fluorine containing internal alkynes (I) affords the corresponding adducts (III)/(IV) in a cis‐selective manner in good to high yields.